Comparison Between Esketamine and Alfentanil for Hysteroscopy: A Prospective, Double-Blind, Randomized Controlled Trial [Response to Letter] - Weng M; Jin Y (Dove Medical Press, 2024)
Mengcao Weng, Yue Jin Department of Anesthesiology, Children’s Hospital, Zhejiang University School of Medicine, National Clinical Research Center for Child Health, Hangzhou, Zhejiang, People’s Republic of ChinaCorrespondence: Yue Jin, Department of Anesthesiology, Children’s Hospital, Zhejiang University School of Medicine, National Clinical Research Center for Child Health, 3333 Binsheng Road, Hangzhou, Zhejiang, 310052, People’s Republic of China, Tel +8613456912018, Email yue_jin@zju.edu.cn